Mortar with refractory waste for passive fire protection - Lima, Paulo Henrique Pereira; França, Sâmara; Maciel, Priscila de Souza; Silva Neto, João Trajano da; Padula, Flávio Renato de Goes; Bezerra, Augusto Cesar da Silva (Ambiente Construído, 2020)
Passive fire protection (PFP) is a field of study applied to the civil construction industry. Refractory brick waste contains elements that can contribute to the properties necessary for PFP. Therefore, this study developed a mortar with refractory brick waste for use as PFP. The authors proposed four formulations with compressive and flexural strength, bulk density and apparent porosity, thermal conductivity, and linear variation that were evaluated before and after heat treatment at 600 °C and 1100 °C. The density did not show significant differences between the formulations. The porosity increased after the heat treatment. The mixture that showed the highest shrinkage at 1100 °C was the one with the highest gypsum content, and all the other ones had shrinkage values lower than the maximum allowed by the C195 standard. The mixture that used the highest amount of gypsum was the one that obtained the lowest thermal conductivity. Therefore, it is concluded that using refractory waste is viable for the development of PFP mortars because they meet the regulatory requirements.